(untitled) (Journal of Naval Architecture and Marine Engineering, 2011)
The objective of this investigation is to study the influence of thermal radiation and magnetic Prandtl number on the steady MHD heat and mass transfer by mixed convection flow of a viscous, incompressible, electrically-conducting, Newtonian fluid which is an optically thin gray gas over a vertical porous plate taking into account the induced magnetic field. The similarity solutions of the transformed dimensionless governing equations are obtained by series solution. It is found that, velocity is reduced considerably with a rise in conduction-radiation parameter (R) or Hartmann number (M) whereas the skin friction is found to be markedly boosted with an increase in M or Magnetic Prandtl number (Pm). An increase in magnetic body parameter (M) or Magnetic Prandtl number (Pm) is found to escalate induced magnetic field whereas an increase in R is shown to exert the opposite effect. Applications of the study include laminar magneto-aerodynamics, materials processing and MHD propulsion thermo-fluid dynamics. DOI: 10.3329/jname.v7i2.5662